PM10 episodes in Greece: Local sources versus long-range transport—observations and model simulations. (2nd January 2017) - Matthaios, Vasileios N.; Triantafyllou, Athanasios G.; Koutrakis, Petros
ABSTRACT: Periods of abnormally high concentrations of atmospheric pollutants, defined as air pollution episodes, can cause adverse health effects. Southern European countries experience high particulate matter (PM) levels originating from local and distant sources. In this study, we investigated the occurrence and nature of extreme PM10 (PM with an aerodynamic diameter ≤10 μm) pollution episodes in Greece. We examined PM10 concentration data from 18 monitoring stations located at five sites across the country: (1) an industrial area in northwestern Greece (Western Macedonia Lignite Area, WMLA), which includes sources such as lignite mining operations and lignite power plants that generate a high percentage of the energy in Greece; (2) the greater Athens area, the most populated area of the country; and (3) Thessaloniki, (4) Patra, and (5) Volos, three large cities in Greece. We defined extreme PM10 pollution episodes (EEs) as days during which PM10 concentrations at all five sites exceeded the European Union (EU) 24-hr PM10 standards. For each EE, we identified the corresponding prevailing synoptic and local meteorological conditions, including wind surface data, for the period from January 2009 through December 2011. We also analyzed data from remote sensing and model simulations. We recorded 14 EEs that occurred over 49 days and could be grouped into two categories: (1) Local Source Impact (LSI; 26 days, 53%) and (2) African Dust Impact (ADI; 23 days, 47%). Our analysis suggested that the contribution of local sources to ADI EEs was relatively small. LSI EEs were observed only in the cold season, whereas ADI EEs occurred throughout the year, with a higher frequency during the cold season. The EEs with the highest intensity were recorded during African dust intrusions. ADI episodes were found to contribute more than local sources in Greece, with ADI and LSI fraction contribution ranging from 1.1 to 3.10. The EE contribution during ADI fluctuated from 41 to 83 μg/m 3, whereas during LSI it varied from 14 to 67 μg/m 3 . Implications : This paper examines the occurrence and nature of extreme PM10 pollution episodes (EEs) in Greece during a 3-yr period (2009–2011). Fourteen EEs were found of 49 days total duration, classified into two main categories: Local Source Impact (53%) and African Dust Impact (47%). All the above extreme PM10 air pollution episodes were the result of specific synoptic prevailing conditions. Specific information on the linkages between the synoptic weather patterns and PM10 concentrations could be used in the development of weather/health-warning system to alert the public that a synoptic episode is imminent.